2014
DOI: 10.1002/jsfa.7023
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion stability, thermo‐rheology and quality characteristics of ground pork patties prepared with soy protein isolate and carrageenan

Abstract: The results indicate that a mixture of SPI and CAR can be effectively used as a functional ingredient to improve the quality of ground pork patties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…The meat industry uses soy ( Glycine max ) preparations in the form of soy flour, soy concentrates and isolates, as well as textured soy. These additives gelate, emulsify, and stabilize the structure of the end product, reducing thermal drip and enhancing its water‐holding capacity . From the nutritional point of view, they are a source of valuable protein.…”
Section: Allergenic Additives and Methods Of Their Detection In Procementioning
confidence: 99%
See 1 more Smart Citation
“…The meat industry uses soy ( Glycine max ) preparations in the form of soy flour, soy concentrates and isolates, as well as textured soy. These additives gelate, emulsify, and stabilize the structure of the end product, reducing thermal drip and enhancing its water‐holding capacity . From the nutritional point of view, they are a source of valuable protein.…”
Section: Allergenic Additives and Methods Of Their Detection In Procementioning
confidence: 99%
“…These additives gelate, emulsify, and stabilize the structure of the end product, reducing thermal drip and enhancing its water-holding capacity. 7 From the nutritional point of view, they are a source of valuable protein. They can be also used as a fat substitutes by reducing the amount of calories in the final product.…”
Section: Allergenic Additives and Methods Of Their Detection In Procementioning
confidence: 99%
“…The results indicated that the combination of soybean protein and polysaccharide can affect the distribution of water in meat paste and improve the oil and water retention performance of meat paste products. Zhou, 2015;Zhao, Zhou, & Zhang, 2019), there was a lack of report on water distribution of raw and cooked minced meat paste prepared with additives, such as plant protein and polysaccharides.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Plant proteins and polysaccharides are often utilized in chopped meat products as meat binders, gelling agents, texture stabilizers or fat substitutes to improve quality (Wijaya, Patel, Setiowati, & Meeren, ). However, in previous work, most of the studies were focused on emulsion stability, WHC, microstructure, and quality characteristics of the heat‐induced meat gelation by additives (Gao, Zhang, & Zhou, ; Zhao, Zhou, & Zhang, ), there was a lack of report on water distribution of raw and cooked minced meat paste prepared with additives, such as plant protein and polysaccharides. Several papers have reported that the low‐field nuclear magnetic resonance (NMR) relaxation is a rapid, noninvasive, and nondestructive method of determining the distribution of water pools with different relaxation time rates in food (Buera, ; Carneiro, Mársico, Júnior, Álvares, & Jesus, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, maintaining moisture, lipids, and food composition as well as improving flavor are necessary components in the applications of meat products. Non-meat protein additives such as whey protein are added to ground pork products primarily to increase product yield, lower production cost, boost water-holding capacity (to enhance juiciness), and improve the textural and functional properties of the meat product [9][10][11].…”
Section: Introductionmentioning
confidence: 99%